'TURREM ET CASTRUM': SOME FRESH THOUGHTS ON THE ROMAN FORTLETS OF THE YORKSHIRE COAST. (20th September 2022) - White, Andrew
Abstract : This paper sets out to interpret the archaeological evidence of the five known Roman fortlets on the Yorkshire coast in a novel way, especially as to the structure and appearance of the sites, and how they were used. In particular it examines the use of stylobate blocks and vertical posts, and makes some comparisons with contemporary small forts and burgi on the Rhine and Danube frontiers, and with maritime defences in Wales. It also looks at evidence for barrack accommodation within the enclosure. The evidence comes from a detailed examination of excavation reports and local histories. Finally, it considers the nature and status of the troops that formed the garrisons here.